THE ROLE OF POLITICAL ACTIVISM IN SHAPING POLICY CHANGE -AN ANALYSIS (International Journal of Food and Nutritional Sciences, 2022)
Political activism plays a pivotal role in shaping policy change by mobilizing public opinion, pressuring policymakers, and influencing the political agenda. This study explores how activism functions as a catalyst for legislative and social reforms through various strategies and methods. Activists raise awareness on critical issues by organizing protests, leveraging media, and utilizing digital platforms to engage and mobilize the public. These efforts help shift public opinion and place pressure on policymakers to address pressing concerns. Through direct lobbying, advocacy, and grassroots organizing, activists create a sense of urgency around specific issues, compelling governments and institutions to prioritize and enact reforms.Furthermore, political activism is instrumental in reshaping the policy agenda by bringing attention to previously marginalized or overlooked issues. Activists build coalitions and networks to amplify their voices, creating a united front that enhances their influence and effectiveness. By institutionalizing changes, activists ensure that new policies are upheld and maintained through regulatory bodies and enforcement mechanisms. Activism also affects the political process by supporting or electing candidates who align with their causes, thereby embedding their priorities within government institutions. The advent of digital platforms has revolutionized activism, enabling rapid mobilization and broadening the reach of campaigns, thus accelerating the pace of change.In conclusion, political activism is a dynamic and essential force in shaping policy change. It drives societal progress by influencing public opinion, pressuring decision-makers, and altering political priorities, ultimately contributing to a more responsive and equitable policy-making process.